The Positive Effects of Mind Mapping Strategy Integration on Improving EFL Learners’ Writing Skill - Kristian Florensio Wijaya (Edukasi, 2023)
The ever-changing nature of modern L2 writing enterprises has added incremental challenges for worldwide EFL learners to continue their productivity, participation, and commitment in this long-lengthy process as they are required to become more proficient L2 writers. Concerning this issue, this study aimed to investigate the positive effects of mind mapping strategy integration in elevating EFL learners’ writing skills. Thus, the researcher reviewed the research results taken from 25 mind mapping strategy studies with the help of a thematic analysis to generate more robust and reliable research results. After analyzing the prior research results forming in 25 previous mind mapping strategy studies, the researcher subsumed them into some main specific themes to ascertain the comprehensibility of the targeted data. Two major specific themes were stipulated namely: (1) Mind mapping strategy enables EFL learners to become more organized L2 writers and (2) Mind mapping strategy transforms EFL learners into more avid L2 writers. It was revealed that mind mapping strategy can potentially elevate EFL learners’ writing motivation, confidence, autonomy, and skills.